Impact of Drain Doping and Biomaterial Thickness in a Dielectrically Modulated Fringing Field Bio-TFET Device - Macambira, Christian N.; Agopian, Paula G. D. [UNESP]; Martino, Joao A.; IEEE (Ieee, 2019)
In this paper, the sensitivity of the modulated fringing field n-type tunneling field effect transistor biosensor (Bio-TFET) was investigated over the influence of drain doping concentration and biomaterial thickness (t(Bio)). It is shown that the sensitivity of the Bio-TFET improves as the drain doping concentration increases up to 1x10(20) cm(-3). The t(Bio) influence over the sensitivity increases for thicker biomaterials up to 40 nm and present lower increment for higher t(Bio). The highest sensitivity value obtained in this work was for a drain doping concentration of 1x10(20) cm(-3) and for biomaterial thickness equal or higher than 40 nm.
Keywords: Biosensor; TFET; Biomaterial thickness; Drain doping; Underlap; Sensitivity; Permittivity